Histopathological and inflammatory response in multiple organs of rats exposed to crack. Issue 9 (2nd September 2022) - Souza, Daniel; Rosarioa, Barbara; Casagrandea, Breno; Viana, Milena; Estadella, Debora; Peres, Rogerio; Seabra Pereira, Camilo Dias; Peres, Rogerio
ABSTRACT: The aim of this study was to investigate histopathological and inflammatory response in liver and kidney of rats after crack exposure. For this purpose, a total of 32 male Wistar rats were distributed into four groups: (G1) and (G2): received 18 mg/kg of body weight (b.w) of crack cocaine, but Group G2 remained 72 h without exposure after the experimental period (5 days). Experimental group 3 (G3): received 36 mg/kg of body weight (b.w) of crack cocaine. Control Group (CTRL): received only the vehicle (DMSO) administered by intraperitoneal (i.p) route for 5 days. The results showed that crack cocaine induced histopathological changes in liver and kidney. Immunohistochemistry data revealed that G2 group showed a higher immunoexpression of Ki-67 in hepatic and renal tissues. Regarding inflammation, the results showed that all groups exposed to crack cocaine decreased the expression of TNF-α, IL-6, and IL-10 in liver and kidney. In summary, our results showed that the subacute doses of crack cocaine used in this study had cytotoxic, and immunosuppressive effects in liver and kidney of rats, especially at 36 mg/kg dose. Since cellular death and inflammation participates in the multi-step process of chemical carcinogenesis, these data offer new insights into potential ways to understand the pathobiological mechanisms induced by crack cocaine in several tissues and organs.